Relocation of earthquakes in the Slat Lake region using the Hypocentroidal Decomposition (HDC) method - Sakarya, Burak. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2017., 2017)
Central Anatolia is a relatively stable region unlike the other regions under the inﬂuence of major tectonic regimes in Turkey. For that reason, the number of seismic instruments installed by regional earthquake monitoring centers are insuﬃcient on de termining and locating earthquakes accurately that are below a certain magnitude in that region. In this study this issue is overcome by building a merged catalog from the data of Kandilli Observatory and Earthquake Research Institute’s (KOERI) perma nent broadband seismic network, temporary broadband seismic network deployment as a part of the ”Continental Dynamics: Central Anatolia Tectonics (CD-CAT)” project, which was installed in the South and Central Anatolian Region along with the data obtained from International Seismological Centre (ISC). The multiple event relocation technique ”mloc” which is based on hypocentroidal decomposition (HDC) algorithm is applied by utilizing the phase arrival time catalog that was speciﬁcally crafted for the study area. Thus, seismic activity surrounding the Salt Lake Fault Zone (SLFZ) and Ecemi¸s Fault Zone (EFZ) in between 1th of June 2013 to 15th of May 2015 are relocated and calibrated. 1-D crustal velocity models are developed for the interest regions, thereby hypocentral parameters as well as the corresponding uncertainties of the total number of 394 earthquakes are extensively evaluated and classiﬁed in order to unravel the tectonic features and seismicity of the Salt Lake Region.
Keywords: Earthquakes -- Slat Lake -- Turkey.